Drug-coated versus bare-metal stents for elderly patients: A predefined sub-study of the LEADERS FREE trial. (15th September 2017) - Morice, Marie-Claude; Talwar, Suneel; Gaemperli, Oliver; Richardt, Gert; Eberli, Franz; Meredith, Ian; Zaman, Azfar; Fajadet, Jean; Copt, Samuel; Greene, Samantha; Urban, Philip
Abstract: Background: The randomized, LEADERS FREE trial showed superior safety and efficacy of a polymer-free DCS vs. a bare metal stent in high-bleeding risk patients with only one month dual antiplatelet treatment. We report characteristics and outcomes of the pre-specified group of elderly patients (aged ≥ 75). Methods: Age > 75 was one of the trial's inclusion criteria. The main additional criteria were: need for oral anticoagulants, recent bleeding, anemia, chronic renal failure and cancer. All patients received 1 month DAPT only. Both primary endpoints (efficacy: clinically driven TLR and safety: composite of cardiac death, MI and stent thrombosis) as well as bleeding were recorded up to 390 days. Results: 1564 elderly patients (63.4% of the population) were enrolled with a mean of 2 inclusion criteria/patient. The primary safety endpoint was reached less frequently in DCS than BMS patients (10.7 vs. 14.3%, p  = 0.03), as was the primary efficacy endpoint (5.8 vs. 10.8% p  = 0.0003). Major bleeding rates were high and similar in both groups (7.3 vs. 8.2%, p  = 0.55). For the 562 (23.4%) patients with age as sole entry criterion, trends were similar for DCS and BMS patients respectively: safety endpoint (7.3%vs.11.4% p  = 0.10) and Cd TLR (4.7 vs. 13.2% p  = 0.0003), but for both groups, major bleeding occurred less frequently than for elderly patients with more comorbid conditions (3.6%vs. 2.8%). Conclusion: Compared to a BMS, use of a DCS together with a short one-month DAPT course was associated with significant safety and efficacy benefits for the elderly patients enrolled in LEADERS FREE .